Distinct evolutionary patterns of endemic and emerging parvoviruses and the origin of a new pandemic virus - Robert A. López-Astacio; Brian R. Wasik; Hyunwook Lee; Ian E. H. Voorhees; Wendy S. Weichert; Oluwafemi F. Adu; Laura B. Goodman; Susan L. Hafenstein; Uwe Truyen; Colin R. Parrish (Proceedings of the National Academy of Sciences, 2026)
Emergence of epidemic viruses in new hosts threatens both human and other animal populations, and often involves virus evolution to overcome barriers that normally prevent efficient infection and spread in that host. After transfer the separated viruses will evolve in parallel as they spread within the original and new hosts. Here we examine the details of a virus involved in such a host-jumping event, where we define the natural evolution of feline panleukopenia virus (FPV) over 60 y, clarify the origins of the new pandemic canine parvovirus (CPV) that arose in the 1970s, and compare the separate evolution of those viruses over 47 y in cats or dogs. Several live-attenuated FPV vaccine viruses originated from early-1960s isolates or were a recombinant of an early virus, and many sequences in databases proved to be vaccine-derived. The sequences of wild viruses showed that FPV-like strains evolved at less than one-third the rate observed for CPV in dogs, and the higher rate of CPV evolution has been consistent since 1979, when a genetic variant became widespread. The common ancestor of the CPV lineage was related to FPVs from Europe and contained several unique host-adaptive capsid changes associated with canine transferrin receptor type-1 binding. Although the FPV vaccine strains are around 60 y old, little selection for antigenic variation was observed. The distinct evolutionary patterns of these closely related viruses circulating for decades in different hosts emphasize the complex evolution associated with viral epidemic emergence and spread in endemic and new hosts.